Analysis of the Collaborative Management Implementation of Conservation Area of the Sultan Syarif Hasyim Forest Park, Riau Province - Matnuril; Junaidi; Abdillah, Muhammad Rasyid; Yesi (Indonesian Journal of Social and Environmental Issues (IJSEI), 2023)
The conservation forest area of Sultan Syarif Hasyim Forest Park, Riau Province an area of 6,172 hectares in the administrative area of Siak Regency, Kampar Regency, and Pekanbaru City. The views (perceptions) of the people that live around this forest area, can provide benefits for economic and social improvement. On the other hand, it cannot be ruled out that the existence of people who have already lived and worked in this forest area have a perception that the area that they control is a place of survival and death. This condition has caused 79% of the total area of this forest to be degraded and converted into oil palm plantations, settlements, social facilities, public facilities, and community business facilities. This research method applies a naturalistic paradigm - qualitative approach design. The data collection technique is through interviews, observation, and documentation study. The data analysis techniques is descriptive with the formal and informal results of the study. The implementation of collaborative management is analyzed from four elements of collaboration, namely; institutional procedures and agreements, leadership, knowledge and resources. The research result shows that the implementation of collaborative management in the conservation forest area of Sultan Syarif Hasyim Forest Park, Riau Province is running optimally on the elements of procedures and institutional agreements, leadership, knowledge and resources. Such conditions can be an example for other forest area managers how to manage forests in a sustainable, ecologically fair manner and provide positive impacts for the community.